An exploration of the experiences of child branch student nurses caring for children and young people who have engaged in Deliberate Self Harm - O'Grady, Carly (2010)
ABSTRACT Various quantitative studies have found generally negative attitudes of healthcare staff towards patients who engage in DSH (Anderson and Standen, 2007; Patterson et al, 2007; McAllister et al, 2002). However, there has been little qualitative research of this subject, therefore, this study has been conducted to further inform current research in relation to attitudes towards DSH. This qualitative piece of research employed semi structured interviews in order to explore the experiences and perceptions of child branch student nurses with regards to caring for children and young people who have engaged in DSH. Five interviews with student nurses uncovered eight interesting themes. Analysis of the themes confirmed that there are negative attitudes towards people who engage in DSH and these attitudes can have an impact upon patient care. Findings also confirmed that there are various reasons for negative attitudes including lack of knowledge, lack of resources or personal feelings or beliefs may also have an impact upon ones attitude. Therefore, a multi faceted approach needs to be taken in order to educate student nurses and supply them with the necessary skills to provide optimum care for children and young people who engage in DSH.